IMF Survey, Volume 35, Issue 01. (IMF Survey; IMF Survey ;, 2006)
IMF cancels debt; Iraq receives new loan; Brazil and Argentina repay IMF loans; Saudi Arabia Article IV summary; Credit booms in transition economies; India's textile and clothing sector; Maghreb parliamentarians; Public awareness of economic issues.